Microwave-assisted Synthesis of CuS/Graphene Composite for Enhanced Lithium Storage Properties. (20th January 2017) - Li, He; Wang, Yunhui; Huang, Jingxin; Zhang, Yiyong; Zhao, Jinbao
Graphical abstract: Highlights: CuS/graphene composite is synthesized via one-pot microwave-assisted method. CuS/graphene composite shows enhanced cycle stability and rate performance. The incorporation of graphene plays a vital role in the electrode. The kinetic mechanisms are investigated by EIS, CV and GITT methods. Abstract: In this work, CuS/graphene (CuS-G) composite is synthesized via one-pot microwave irradiation method under ambient conditions. As anode material for lithium ion batteries, the CuS-G composite delivers a significantly enhanced reversible capacity and charge/discharge cycle stability compared with pristine CuS. A capacity of 348 mAh g −1 can be maintained after 1000 cycles at the current density of 2.0 A g −1 . Electrochemical impedance spectroscopy (EIS) along with cyclic voltammetry (CV) and galvanostatic intermittent titration technique (GITT) measurements indicate that the incorporation of graphene sheets reduces the contact resistance and enhances lithium ion transfer rate during the electrochemical lithium insertion/extraction remarkably. Thus, as-prepared CuS spheres can be a promising anode material for high performance lithium ion batteries.